Kinerja pengelolaan arsip Kantor Pelayanan Utama Bea dan Cukai Tipe A Tanjung Priok - Kartini Kartini; Sukaesih Sukaesih; Agung Budiono (Jurnal Kajian Informasi dan Perpustakaan, 2019)
The dynamic records management of goods import notification documents is an essential activity in storing data on goods entering Indonesia. The Main Service Office for Customs and Excise Type A Tanjung Priok as a government agency is obliged to record incoming goods as trade data. This study aimed to determine the dynamic records management of imported goods notification (PIB) documents on customs activities for the success of dwelling time at the Main Service Office for Customs and Excise Type A Tanjung Priok. The research method used a case study through a qualitative approach. Data collection techniques used were observation, interviews, and document study. The results showed the process of recording imported goods document notifications through the process of creating and receiving import documents began from the delivery of imported goods document notification (PIB) to the Customs Office. Submitting of the notifications was through the Electronic Data Exchange (PDE) system to the determination of the document path for 4 minutes. The organization process of notification documents for imported goods goes through 5 stages, namely, distribution of documents, the process of completing customs administration of imported goods documents, storing the processed documents, rediscovering documents, and maintaining imported goods documents. The process of dissemination at the Customs and Excise agency itself is inseparable from a system called Customs-Excise Integrated System and Automation (CEISA). The system is an integrated system of all Directorate General Customs and Excise services to all public service users. Their can access this system without limited space and place.